A Conversation with ... South African Artist Christine Dixie on the Exhibition opening: "To Be King" (A Conversation with ..., 2022)
The Africa Multiple Cluster of Excellence has invited South African artist Christine Dixie to show her multimedia installation "To Be King" at Iwalewahaus. The artist based in Johannesburg set up her installation and celebrated the exhibition opening on Wednesday, 11 May 2022. The exhibition will run until the end of July. The interview was conducted by Nicole Klug.